Pengembangan Media Story Dice Berbasis Gamifikasi untuk Kemampuan Kreativitas Menulis Cerpen - Syahda Khairunnisa Sugiharjo; Rina Devianty (Department of Indonesia Language and Literature Teaching, UIN Syarif Hidayatullah Jakarta, 2026)
The creativity of writing short stories for students still faces obstacles, especially in coming up with ideas, developing plots, and integrating story elements as a whole. This condition shows the need for media that is able to provide concrete stimulus and encourage the exploration of creative ideas. This research aims to develop gamification-based Story Dice media that integrates characters, settings, conflicts, and characterization and tests its feasibility, practicality, and effectiveness in developing creativity in writing short stories. The research uses the Research and Development method with the ADDIE model. The subjects of the study were 37 students in grade VII MTs of the Worship Education Foundation. Data was collected through expert validation, student and teacher response questionnaires, and writing tests with a one-group pretest-posttest design. The results of the study showed that Story Dice obtained an average feasibility rate of 94% and was considered practical to use. This media helps students get an initial stimulus, combine story elements in a more varied way, and develop ideas into more targeted short stories. Writing ability increased from an average score of 61 to 89 with an N-Gain of 0.71 in the high category. These findings suggest that Story Dice's randomization mechanism can reduce the initial barrier to finding ideas while encouraging creativity in short story writing.